Digitization of Precipitation: Digitalisasi Curah Hujan - Obidova, Dilnoza; Hamdamova, Dinora; Norboyev, Nodir (Universitas Muhammadiyah Sidoarjo, 2024)
In addressing the challenges posed by outdated and insufficiently documented urban drainage, irrigation, and storm systems, this study aims to revolutionize urban infrastructure through digitalization. Leveraging insights from 25 invited experts representing various organizations, including highway committees, city administration, and city improvement departments, the research focuses on the city of Tashkent. Employing geodesic methodologies, the team meticulously documented the locations and conditions of underground facilities, utilizing city maps and visual aids provided by specialists. The resulting digital database, curated by geodesists, identifies responsible personnel, object types, and areas requiring attention. This innovative initiative not only fills crucial knowledge gaps but also lays the foundation for enhanced maintenance strategies and resource optimization, offering a paradigm shift in urban planning and management. Highlights: Comprehensive Digital Mapping: The study employs advanced geodesic techniques to create a detailed digital map of aging drainage, irrigation, and storm systems, offering a comprehensive overview of their current conditions. Knowledge Integration from Diverse Experts: Gathering insights from 25 experts across various organizations, the research consolidates valuable information on underground facilities, enabling a holistic understanding of the urban infrastructure challenges. Strategic Resource Optimization: The resulting digital database not only identifies critical maintenance areas but also assigns responsibility, paving the way for strategic resource allocation and efficient urban infrastructure management. Keyword: Urban Infrastructure, Digitalization, Drainage Systems, Geodesic Mapping, Resource Optimization